A Disaggregated Approach to Modelling UK Labour Force Participation - Joanne Cutler; Kenny Turnbull (Bank of England, External Monetary Policy Committee Unit, 2001)
Fluctuations in the labour force participation rate in the short to medium run are an important determinant of the cyclical behaviour of the unemployment rate, and hence wage pressures in the economy. This paper takes a closer look at the cyclical behaviour of labour force participation in the United Kingdom over the last 15 years with a view to producing short term projections for the next two years. We model labour participation rates at a disaggregated level, for males and females separately. Because the trends in male and female participation rates have been quite different, a disaggregated approach is more likely to pick up reliable trends and therefore cyclical variations. We find evidence of procyclical movements in participation rates for both men and women, and the response to changes in the output gap is significant. Conditional on projections for the output gap made at the end of 2000, we estimate that the participation rate will continue to increase - by around +0.2pp over the next two years - but at a slower pace than in the recent past.
Keywords: 330